2005
DOI: 10.3201/eid1107.040724
|View full text |Cite
|
Sign up to set email alerts
|

Cervids as Babesiae Hosts, Slovenia

Abstract: We describe cervids as potential reservoir hosts of Babesia EU1 and B. divergens . Both babesial parasites were found in roe deer. Sequence analysis of 18S rRNA showed 99.7% identity of roe deer Babesia EU1 with the human EU1 strain. B. divergens detected in cervids was 99.6% identical to bovine B. divergens .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 14 publications
9
94
2
Order By: Relevance
“…The parasites were identified by nested PCR, and sequence analysis of the 18SrRNA showed 99.7% of identity of the roe deer Babesia EU1 with the human strain EU1. The Babesia divergens detected in cervids was 99.6% identical to bovine B. divergens, which suggests that the roe deer and red deer may serve as a reservoir for B. divergens (Duh et al, 2005). Therefore, our findings support that deer may be a reservoir of bovine Babesia species.…”
supporting
confidence: 66%
“…The parasites were identified by nested PCR, and sequence analysis of the 18SrRNA showed 99.7% of identity of the roe deer Babesia EU1 with the human strain EU1. The Babesia divergens detected in cervids was 99.6% identical to bovine B. divergens, which suggests that the roe deer and red deer may serve as a reservoir for B. divergens (Duh et al, 2005). Therefore, our findings support that deer may be a reservoir of bovine Babesia species.…”
supporting
confidence: 66%
“…In contrast, Babesia sp. EU1 which has repeatedly been identified in game or in ticks in Europe (Casati et al, 2006;Duh et al, 2005a;Duh et al, 2005b;Hilpertshauser et al, 2006 and this work) and which also has been reported in three splenectomized human patients (Haselbarth et al, 2007;Herwaldt et al, 2003), differs by 3% in this gene sequence. The analyses of part of the 28S rRNA gene and of the more variable locus, the rDNA ITS, revealed again a high similarity, but the isolates from cattle could clearly be differentiated from those of free-ranging ruminants (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…EU1, and first studies revealed prevalences of up to 30% (Bonnet et al, 2007;Duh et al, 2005b;Hoby et al, 2007b). Interestingly, the parasites seem to have a low virulence in roe deer, and it may be speculated that roe deer acts as a reservoir for the parasite affecting chamois.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. divergens has also been found in humans and wild ruminants, roe (Capreolus capreolus), and red deer (Cervus elaphus), Duh et al 2005;Zintl et al 2011), although the designation of red deer as a host is still under discussion. B. divergens is endemic in the southern part of Belgium (Losson and Lefevre 1989) but is considered absent from other parts of the country (Saegerman et al 2007).…”
Section: Introductionmentioning
confidence: 99%